THE USE OF AUGMENTED REALITY IN COMMAND AND CONTROL SITUATION AWARENESS - Le Roux, Willem (Scientia Militaria - South African Journal of Military Studies, 2011)
Augmented reality is not completely new technology, but rather an interesting combination of existing technologies, facilitated by the rapid progress made on ultra-portable devices such as smart cellular telephones. It has the potential to enhance the situation awareness of military operators. This study identifies possible uses of augmented reality in command and control applications with specific attention to situation awareness in the South African context. Applications across the different command and control functions, as well as at the different levels of military operations are considered. The article concludes with some concept definitions for augmented reality applications.